The Effect of Leverage, Return on Asset (roa), and Company Size on Company Value with Good Corporate Governance as Moderating Variables (study on Manufacturing Companies) - Listiorini, Listiorini; Putri, Rani Andira (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2022)
This research was conducted with the aim to determine the effect of firm leverage, return on asset and firm size on firm value with good corporate governance as a moderating variable. This type of research is quantitative research with causality approach. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. Sampling technique using purposive sampling method with a sample of 55 companies with 5 years observasion so that the total sample of 275. The method of analysis of this study uses multiple linear regression and moderation regression analysis. The results of this research indicates that leverage significantly influence firm value and return on asset, while firm size do not significantly influence firm value, and good corporate governance does not moderated the relationship of leverage, return on asset and firm size to firm value in manufacturing companies listed in Indonesia Stock Exhange in year of 2015-2019.